Risk factors for major adverse cardiovascular events after the first acute coronary syndrome - Marjo Okkonen; Aki S. Havulinna; Olavi Ukkola; Heikki Huikuri; Arto Pietilä; Heli Koukkunen; Seppo Lehto; Juha Mustonen; Matti Ketonen; Juhani Airaksinen; Y. Antero Kesäniemi; Veikko Salomaa (Annals of Medicine, 2021)
AbstractAims To evaluate risk factors for major adverse cardiac event (MACE) after the first acute coronary syndrome (ACS) and to examine the prevalence of risk factors in post-ACS patients.Methods We used Finnish population-based myocardial infarction register, FINAMI, data from years 1993–2011 to identify survivors of first ACS (n = 12686), who were then followed up for recurrent events and all-cause mortality for three years. Finnish FINRISK risk factor surveys were used to determine the prevalence of risk factors (smoking, hyperlipidaemia, diabetes and blood pressure) in post-ACS patients (n = 199).Results Of the first ACS survivors, 48.4% had MACE within three years of their primary event, 17.0% were fatal. Diabetes (p = 4.4 × 10−7), heart failure (HF) during the first ACS attack hospitalization (p = 6.8 × 10−15), higher Charlson index (p = 1.56 × 10−19) and older age (p = .026) were associated with elevated risk for MACE in the three-year follow-up, and revascularization (p = .0036) was associated with reduced risk. Risk factor analyses showed that 23% of ACS survivors continued smoking and cholesterol levels were still high (>5mmol/l) in 24% although 86% of the patients were taking lipid lowering medication.Conclusion Diabetes, higher Charlson index and HF are the most important risk factors of MACE after the first ACS. Cardiovascular risk factor levels were still high among survivors of first ACS.